Efficacy of combination therapy with mirabegron for anticholinergic-resistant neurogenic bladder videourodynamic evaluation - Wada, Naoki (Hinyokika kiyo. Acta urologica Japonica, 2015)
Using a videourodynamic study, we examined the efficacy of combination therapy with mirabegron for anticholinergic-resistant neurogenic bladder. We retrospectively studied 7 patients with neurogenic bladder (5 males and 2 females) who had detrusor overactivity (DO) or low compliance bladder (＜10 ml/cmH2O) despite taking anticholinergic medication. Bladder deformity was categorized from G0 to G3 by Ogawa's classification. Mean age of study patients was 51 years (25-76). Underlying diseases were spinal cord injury in 3 patients, spina bifida in 2, spinal cord infarction in 1, and post-radical hysterectomy in 1. Preceding anticholinergic medication was solifenacin 5 mg in 1 patient, solifenacin 10 mg in 5, and tolterodine 4 mg in 1. Before mirabegron, bladder deformity was G1 in 4 patients, G2 in 1 and G3 in 2, and vesicoureteral reflux (VUR) was detected in 3 patients. Five and 4 patients had detrusor overactivity and low compliance bladder, respectively. Videourodynamic study was reevaluated at a mean of 7 months (2- 12 months) after mirabegron. After mirabegron, urinary incontinence was improved in all patients. G3 bladder deformity was improved to G2 and G1 in one patient each, and VUR disappeared in all 3 patients. DO disappeared in 2 of the 5 patients, and bladder compliance was improved in all 4 patients with low compliance bladder. In conclusion, combination therapy of mirabegron is effective and beneficial for anticholinergic-resistant neurogenic bladder